2020
DOI: 10.1088/1361-6501/abc027
|View full text |Cite
|
Sign up to set email alerts
|

Heated thin film gauge arrangements to reduce uncertainty in transient heat transfer measurements

Abstract: This paper describes the development of heated double-sided thin film gauge configurations for transient heat transfer measurements. By heating the substrate it is possible to measure the heat flux over a range of surface temperatures and deduce the adiabatic wall temperature and the external heat transfer coefficient. The accuracy of the measurement depends on the stability of the regression of heat flux against wall temperature and can be improved by extending the range of wall temperature over which the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Given the good agreement between the 1D analytical solution and 3D thermal model over the short test window, the three-dimensional diffusion effects of heat can therefore be neglected. Usandizaga [14] also reported that lateral conduction is negligible if the test time t is sufficiently short such that αt << l 2 where l is the lateral length over which significant temperature variations could occur.…”
Section: Comparison With 1d Analytical Solutionsmentioning
confidence: 97%
See 2 more Smart Citations
“…Given the good agreement between the 1D analytical solution and 3D thermal model over the short test window, the three-dimensional diffusion effects of heat can therefore be neglected. Usandizaga [14] also reported that lateral conduction is negligible if the test time t is sufficiently short such that αt << l 2 where l is the lateral length over which significant temperature variations could occur.…”
Section: Comparison With 1d Analytical Solutionsmentioning
confidence: 97%
“…A thin, high resistivity and high length-width ratio thin-film gauge is desirable for good voltage-temperature sensitivity. The design and dimensions of the thin-film gauges have been optimised through numerous studies carried out at Oxford [11,12,14]. Serpentine gauges developed by Collins [12] were found to give erroneous measurements due to strain effects coupled with temperature effects.…”
Section: Sensitivity Of a Thin-film Gaugementioning
confidence: 99%
See 1 more Smart Citation